An Analysis of Academic Library 3D Printing LibGuides. Issue 2 (3rd July 2017) - Horton, Jennifer J.
ABSTRACT: 3D Printing is increasingly becoming a popular service provided by academic libraries throughout the United States. Many patrons have little or no awareness of this subject matter, so library staff have created LibGuides to promote resources. One hundred LibGuides from academic libraries were analyzed to find which types of resources and which specific titles are being promoted surrounding the subject of 3D printing. Three types of resources emerged in this study: 3D printing and 3D modeling software titles, 3D model repositories, and books related to 3D printing. This article lists and analyzes 3D printing resources.